2020
DOI: 10.3390/w12040953
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Source of Dissolved Organic Matter in Lake Hulun, A Large Shallow Eutrophic Steppe Lake in Northern China

Abstract: Lake Hulun, the fifth largest lake in China, is a typical eutrophic steppe lake located in the Hulun Buir Prairie. The dissolved organic matter (DOM) in the water of Lake Hulun has a high concentration. However, little is known about the occurrence characteristics and source of the DOM in Lake Hulun. The spatial and temporal distribution characteristics of DOM concentration in Lake Hulun were thoroughly surveyed, and the optical characteristics, fluorescence components and sources of DOM were analyzed by excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Hulun Lake (48.55°-49.33°N, 116.97°-117.81°E) is also known as Dalai Lake. The Hulun Lake basin (including Halaha and Hailar River Basins) is located in China and Mongolia and has an area of 2.92 × 10 5 km 2 , of which the area in China is 1.08 × 10 5 km 2 , accounting for 37% of the total area (Wang et al 2020). The length, width, circumference, and average water depth of Hulun Lake is 93 km, 32 km, 447 km, and 5.7 m, respectively (Li et al 2019).…”
Section: Study Areamentioning
confidence: 99%
“…Hulun Lake (48.55°-49.33°N, 116.97°-117.81°E) is also known as Dalai Lake. The Hulun Lake basin (including Halaha and Hailar River Basins) is located in China and Mongolia and has an area of 2.92 × 10 5 km 2 , of which the area in China is 1.08 × 10 5 km 2 , accounting for 37% of the total area (Wang et al 2020). The length, width, circumference, and average water depth of Hulun Lake is 93 km, 32 km, 447 km, and 5.7 m, respectively (Li et al 2019).…”
Section: Study Areamentioning
confidence: 99%
“…The redox conditions of the active fluvial drainage system developed under oxidizing conditions. Reducing conditions occur at the edge of abandoned fluvial drainage systems where oxbow and cut lakes form in a similar manner to that of perennial lakes regarding the sedimentology and sediment chemistry (Tables 4 and 5) [145,146,202,203]. Precise markers of shallow ground water levels, which are quite common to fluvial flood plains, are found within the realm of soil types.…”
Section: Confined and Unconfined Fluvially Driven Processesmentioning
confidence: 96%
“…The Kathmandu Valley, Nepal, is an intermontane basin in the center of a large syncline of the Lesser Himalayas filled with three units reflecting an alluvial through lacustrine depositional environment during the Pliocene-Pleistocene [143]. This sort of basin has always attracted the attention of economic geologists in search of fossil fuels due to the high TOC values of their basin fill, which is attested to by the dull grey and black rock color of some of their fine-grained clastic sediments hosting either coalified or bituminous matter [136,[144][145][146] (Figure 9a,b).…”
Section: Lacustrine Processes and Their Landformsmentioning
confidence: 99%
“…Hoyer et al showed that the abundance of waterbird species richness was positively correlated with the size of the water body [ 12 ]. Additionally, the nutritional status of the lake had a significant positive impact on the diversity of waterbirds [ 13 , 14 , 15 ]. The encroachments on the river due to built-up areas, bridges, etc.…”
Section: Introductionmentioning
confidence: 99%